Australia : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2003)
Australia's economy has continued to perform remarkably well, despite encountering major adverse shocks. Fiscal policy, with an objective of maintaining a balanced budget, will help support the economy. Maintaining a sound and stable macroeconomic environment is essential. Reforms of the personal income tax system are critical elements. A comprehensive reform of the complex system of income support payments would provide stronger incentives for labor force participation. Maintenance of competitive product markets will contribute to faster innovation and productivity and income growth. The financial system is sound.